Modeling of Mn/ROAD Test Sections with the CRREL Mechanistic Pavement Design Procedure. - Bigl, Susan R.; Berg, Richard L. (1996)
The U.S. Army Cold Regions Research and Engineering Laboratory is developing a mechanistic pavement design procedure for use in seasonal frost areas. The procedure was used to predict pavement performance of some test sections under construction at the Mn/ROAD facility. Simulations were conducted in three phases, investigating the effects on predictions of water table position, subgrade characteristics, asphalt model, and freeze season characteristics. The procedure predicted significantly different performance by the different test sections and highly variable results depending on the performance model applied. The simulated performance of the tests sections also was greatly affected by the subgrade conditions, e.g., density, soil moisture, and water table depth. In general, predictions for the full depth asphalt sections indicate that they will not fail due to cracking, but two of the three criteria for subgrade rufting indicate failure before the five or 10 year design life of the sections. Conventional sections are predicted not to fail due to subgrade rutting; however, sections including the more frost susceptible bases in their design are predicted to fail due to asphalt cracking relatively early in their design life, and sections with nonfrost susceptible bases are predicted to fail towards the end of the design life.